Characterization of Zahari Zograph's nave wall paintings in the church "The nativity of the virgin" of Rila Monastery (Bulgaria) by vibrational spectroscopy and SEM–EDX analysis. Issue 2 (15th December 2017) - Yancheva, Denitsa; Tapanov, Stefan; Velcheva, Evelina; Stamboliyska, Bistra; Glavcheva, Zornitza; Stoyanov, Simeon; Haralampiev, Nikifor; Fischer, Dieter; Lederer, Albena
ABSTRACT: An analytical study on the nave mural paintings of the church "The Nativity of the Virgin" of Rila monastery, Bulgaria, painted by Zahari Zograph was carried out. Vibrational spectroscopy was applied to identify the pigments and organic materials used in the mural paintings. To complement the spectral information, elemental composition of the samples was determined by SEM-EDX. The data showed that smalt with carbohydrate binder was applied for the blue background, green colour was executed by green earths and red-orange colour – by red lead. Azurite is the pigment used to paint the blue colour of the saints' hoods. The mordant for gilding was prepared of drying oil, resin and siccative metal oxides as evidenced by SEM-EDX, ATR-FTIR and pyrolysis GC-MS analysis. The use of azurite is related to Zahari Zograph's works as it was not found in any of the previously studied murals in the church painted by other artists.